Direct Sagittal CT in the Evaluation of Temporal Bone Disease - Mafee, Mahmood F.; Kumar, Arvind; Tahmoressi, Christina N.; Levin, Barry C.; James, Charles F.; Kriz, Robert; Capek, Vlastimil (American Journal of Neuroradiology, 1988)
The human temporal bone is an extremely complex structure. Direct axial and coronal CT sections are quite satisfactory for imaging the anatomy of the temporal bone; however, many relationships of the normal and pathologic anatomic detail of the temporal bone are better seen with direct sagittal CT sections. The sagittal projection is of interest to surgeons, as it has the advantage of following the plane of surgical approach. This article describes the advantages of using direct sagittal sections for studying various diseases of the temporal bone. The CT sections were obtained with the aid of a new headholder added to our GE CT 9800 scanner. The direct sagittal projection was found to be extremely useful for evaluating diseases involving the vertical segment of the facial nerve canal, vestibular aqueduct, tegmen tympani, sigmoid sinus plate, sinodural angle, carotid canal, jugular fossa, external auditory canal, middle ear cavity, infra- and supralabyrinthine air cells, and temporomandibular joint.